Intangible Assets and Financial Management Decisions on the Example of WSE Companies - Pastusiak, Radosław; Bolek, Monika; Lyroudi, Katarina (Acta Universitatis Lodziensis. Folia Oeconomica, 2016)
This paper investigates the companies listed on WSE in the context of intangibles and financial management. If a company decides to build its strategy on innovation, it will have to manage the finances according to some rules specific for innovation based entities. The value of a company should grow as a result of joint decisions in the field of innovation and finances. Specifically, this paper investigates the influence of company’s intangibles on its liquidity strategy, cash management, profitability, debt capacity and market value. As a result of analysis it has been found that there exist relationships among those factors, indicating that innovation based strategy should be supported by financial decisions that enable the company to increase its value.